PENGARUH LIABILITAS DAN EKUITAS TERHADAP PERTUMBUHAN BRI SYARIAH TAHUN 2016-2020 - Khairani, Wanda; Syah, Rahmat; Vebrina, Dinda (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Companies are generally established with the aim of making a profit. Profit growth is influenced by the provision and use of capital properly. If this goes well, it will be able to maximize the profits earned by the company. The company's capital comes from two sources, namely external sources (as liabilities) and internal (as equity). The formulation of the problem in this study is whether there is a partial and simultaneous effect of liabilities and equity on BRI Syariah profits in 2016-2020. This study aims to determine the effect of liabilities and equity partially or simultaneously on BRI Syaraiah's profits in 2016-2020. This type of research is a quantitative research with data sources used are secondary data taken through the website www.brisyariah.co.id as many as 58 samples. The data analysis technique used is descriptive statistical test, normality test, classic assumption test, hypothesis testing and multiple linear regression analysis using SPSS version 23. The partial results of the study (t test) state that the liability variable has tcount ttable (2.328 1.674) and a significance value (0.024) 0.05, so it can be concluded that the liability variable affects earnings. However, the equity variable has tcount ttable (-1.016 1.674) and a significance value (0.314) 0.05, it is concluded that equity has no effect on earnings. The results of the study simultaneously (F test) stated that the liability variable and equity variable had an effect on profit, by comparing Fcount Ftable (3.282 3.17). Based on the results of the coefficient of determination it is known that the value of Adjusted R Square has a value of 0.131 or 13.1%. The Adjusted R Square value shows that the liabilities and equity variables affect profit by 0.131 or 13.1% and the remaining 0.869 or 86.9% is influenced by other variables not discussed in this study.